2002
DOI: 10.1046/j.1365-2648.2000.02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing surgical practice through feedback of performance data

Abstract: The findings indicate that if change in practice is to be achieved by the feedback of performance data, then the process of feedback should be active and within a normative re-educative approach to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In international studies, the compliance with infection control precautions is usually reported to remain suboptimal (Larson & Kretzer 1995, Pittet et al. 2000, Reilly et al. 2002, Flin et al.…”
Section: Introductionmentioning
confidence: 99%
“…In international studies, the compliance with infection control precautions is usually reported to remain suboptimal (Larson & Kretzer 1995, Pittet et al. 2000, Reilly et al. 2002, Flin et al.…”
Section: Introductionmentioning
confidence: 99%
“…In our review of this literature we found seven studies that utilized weekly feedback; all reported that weekly feedback changed clinician behavior (Boekeloo et al 1990; Buffington et al 1991; Cohen et al 1982; Everett et al 1983; Manheim et al 1990; Martin et al 1980; Sommers et al 1984). Positive effects were reported among studies employing monthly (Andrews et al 2001; Buntinx et al 1993; Chassin & McCue 1986; Kiefe et al 2001; McPhee et al 1989; Reilly et al 2002) and quarterly feedback (Gutierrez et al 1994; Jones et al 1996; Lomas et al 1991; Raasch et al 2000), although negative or nonsignificant findings were also noted (Lomas et al 1991; Sondergaard et al 2003; Wones 1987). With the exception of one study (Dijkstra et al 2004), semiannual feedback did not lead to changes in clinician behavior (Eccles et al 2001; Hillman et al 1998; Horner et al 2005).…”
mentioning
confidence: 97%
“…However, systematic reviews of controlled trials and before-after studies of audit and other behavioral change mechanisms show mixed results [10,11,12,13]. A few articles have addressed the effect of audit on the practice of surgery [14,15,16,17,18,19,20,21], but we have not found studies conducted to assess the effect of audit on the surgeons’ clinical practice in the neurosurgical literature.…”
Section: Introductionmentioning
confidence: 85%